p21(Cip1) expression is increased in ambient oxygen, compared to estimated physiological (5%) levels in rat muscle precursor cell culture - Lees, S. J. (Cell Prolif, 2008)
Abstract.  Objective: While it is common practice to culture cells in the presence of ambient oxygen (~21% O(2)), O(2) level observed in the physiological environment is often much lower. Previous efforts to culture a variety of different stem cells, including muscle precursor cells (MPC), under O(2) conditions that better mimic in vivo conditions have resulted in enhanced proliferation. In the present study, we hypothesized that 20% O(2) in culture represents a sufficient stimulus to cause increased expression of two key negative regulators of the cell‐cycle Cip/Kip family of cyclin‐dependent kinase inhibitors, p21(Cip1) and p27(Kip1), in MPCs. Materials and methods: MPCs were isolated from Fischer 344 × Brown Norway F(1) hybrid male rats and O(2) was adjusted in culture using a tri‐gas incubator. Results: 5‐Bromo‐2′‐deoxyuridine incorporation, cell number and nuclear proliferating cell nuclear antigen expression were all decreased after 48 h culture in 20% O(2), compared to 5% O(2). Twenty per cent O(2) had no effect on either p27(Kip1) promoter activity or protein expression. Although p21(Cip1) promoter activity remained unchanged between 5% and 20% O(2), there were significant increases in both p21(Cip1) mRNA and protein expression. Furthermore, 20% O(2) caused an increase in p21(Cip1) mRNA stability and p53 transcription factor activity. Conclusion: These findings are considered important because they reveal p21(Cip1) as a critical regulatory protein that needs to be considered when interpreting proliferation data from MPCs studied in culture. In addition, O(2)‐dependent regulation of MPC proliferation is relevant to conditions, including sarcopenia, heart failure, cancer and muscular dystrophy, where increased oxidative stress exists.